PENGARUH KEPERCAYAAN, KEMUDAHAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI SITUS ONLINE STORE LAZADA (Survei pada Mahasiswa Universitas Slamet Riyadi Surakarta) - Yuli Nur Pratiwi; Suprihatmi Sri Wardiningsih & Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
The purpose of this research is to analyze the significance of the influence of trust, convenience and price on purchasing decisions through Lazada's online store site to students of Universitas Slamet Riyadi Surakarta. This research uses survey method, the type of data used is qualitative data and quantitative data, the data sources used are primary data and secondary data. The population in this study were all students of Universitas Slamet Riyadi Surakarta who had made purchases through the Lazada application. The number of samples in this study were 70 people, the sampling technique used was purposive sampling. Data collection method used: questionnaire. Data analysis techniques used were validity test, reliability test, classic assumption test, and multiple linear regression analysis. The results of the research on the confidence variable did not significantly influence the purchase decision. The results of youth variable research have a significant effect on purchasing decisions. The results of the variable price study have no significant effect on purchasing decisions. The results of the study concluded that trust, convenience, and price have a significant effect on purchasing decisions. Keywords: trust, convenience, price, purchase decision